Listening to children : being and becoming - Davies, Bronwyn, 1945- (London : Routledge, 2014)
Through a series of exquisite encounters with children, and through a lucid opening up of new aspects of poststructuralist theorizing, Bronwyn Davies opens up new ways of thinking about, and intra-acting with, children. This book carefully guides the reader through a wave of thought that turns the known into the unknown, and then slowly, carefully, makes new forms of thought comprehensible, opening, through all the senses, a deep understanding of our embeddedness in encounters with each other and with the material world. This book takes us into Reggio-Emilia-inspired Swedish preschools in Sweden, into the author's own community in Australia, into poignant memories of childhood, and offers the reader insights into: new ways of thinking about children and their communities; the act of listening as emergent and alive; ourselves as mobile and multiple subjects; the importance of remaining open to the not-yet-known. Defining research as diffractive, and as experimental, Davies' relationship to the teachers and pedagogues she worked with is one of co-experimentation. Her relationship with the children is one in which she explores the ways in which her own new thinking and being might emerge, even as old ways of thinking and being assert themselves and interfere with the unfolding of the new. She draws us into her ongoing experimentation, asking that we think hard, all the while